Comparative study on antibacterial characteristics of the multiple liver expressed antimicrobial peptides (LEAPs) in teleost fish - Liu, Xun; Hu, Ya-Zhen; Pan, Yi-Ru; Liu, Jia; Jiang, You-Bo; Zhang, Yong-An; Zhang, Xu-Jie (Frontiers in Immunology, 2023)
Liver-expressed antimicrobial peptides (LEAPs), a family of antimicrobial peptides, are widely distributed in vertebrates. LEAPs include two types, named LEAP-1 and LEAP-2, and many teleost fish have more than one isoform of LEAP-2. In this study, LEAP-2C from rainbow trout and grass carp were discovered, both of which consist of 3 exons and 2 introns. The antibacterial functions of the multiple LEAPs were systematically compared in rainbow trout and grass carp. The gene expression pattern revealed that rainbow trout and grass carp LEAP-1, LEAP-2A, LEAP-2B and/or LEAP-2C were differentially expressed in various tissues/organs, mainly in liver. After bacterial infection, the expression levels of LEAP-1, LEAP-2A, LEAP-2B and/or LEAP-2C in the liver and gut of rainbow trout and grass carp were up-regulated to varying degrees. Moreover, the antibacterial assay and bacterial membrane permeability assay showed that rainbow trout and grass carp LEAP-1, LEAP-2A, LEAP-2B and LEAP-2C all have antibacterial activities against both Gram-positive and Gram-negative bacteria with varying levels in part through membrane rupture. Furthermore, cell transfection assay showed that only rainbow trout LEAP-1, but not LEAP-2, can lead to the internalization of ferroportin, the only iron exporter on cell surface, indicating that only LEAP-1 possess iron metabolism activity in teleost fish. Taken together, this study systematically compared the antibacterial function of LEAPs in teleost fish and the results suggest that multiple LEAPs can enhance the immunity of teleost fish through different expression patterns and different antibacterial activities to various bacteria.